Managerial Cultures in UK Further and Vocational Education Transforming Techno-Rationalism into Collaboration - Baldwin, John.; Raven, Neil.; Webber - Jones, Robin (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book offers unique insights into the impact of the rise of a managerialist culture in Further Adult and Vocational Education (FAVE) in England. It will also raise awareness of the consequences of the imposition of top-down models of educational change and improvement upon the practices of educational leaders, middle and senior managers and policy professionals across the FAVE sector. The overall aim of this book is to understand the language, policies, values and approaches currently espoused in post-16 learning. Often these are driven by, or measured by, technical-rational approaches which can have a negative impact on individuals working in the sector, lead to a narrowing of the curriculum and range of assessment opportunities, and do not support student progression. The authors propose tentative, researched, and evidence-based suggestions for new ways of working which might, ultimately, have a significant benefit to post-16 learning. The book will appeal to those engaged in researching education - either as academics, policy makers, trainees, or practitioners who are interested in ways of reflecting on, researching into, and improving practice. John Baldwin is now semi-retired, continuing with work in further education and in researching practice to support people to progress to higher education. He began his career in education as a business and law Lecturer at Stamford College, UK, and progressed onto being the Head of the Business Studies Department. Subsequently, he became Director of Curriculum and over many years was responsible for most departments in the college. Neil Raven is an independent researcher and evaluation consultant with over 22 years of experience in the development, management and evaluation of educational projects and programmes. He is also Visiting Lecturer at the University of Bristol, UK, and has published widely on the subjects of educational equality and fair access. Robin Webber-Jones is currently Head of Apprenticeships at the University of Derby, UK. He has spent 17 years working and researching in the skills sector. He has also had a number of leadership positions in Further Education Colleges. Furthermore, he has undertaken a number of strategic and development roles, including chairing regional widening participation groups, working with government departments, serving on the boards of a number of education charities, and being involved in large social mobility projects.
Chapter 1: Introduction -- Chapter 2: The Policy Conundrum -- Chapter 3: If you can't count it it doesn't count? -- Chapter 4: Students and Employers as co-designers of their own learning -- Chapter 5. Who has the power? Leading education -- Chapter 6. Collaboration - developing common languages -- Chapter 7. So What Next?
Keywords: Professional education; Vocational education; Education and state; Continuing education; Teaching; Professional and Vocational Education; Educational Policy and Politics; Lifelong Learning; Didactics and Teaching Methodology